1986
DOI: 10.1620/tjem.150.117
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid binding in human artery.

Abstract: Mineralo- and glucocorticoid binding in cytosol of surgically obtained human arteries and umbilical arteries were analyzed. Scatchard analysis of glucocorticoid binding in femoral and umbilical arteries revealed the binding parameters of Kd = 4.3, 8.2 X 10(-9) M; Bmax = 42, 90 fmol/mg protein, respectively. Scatchard analysis of mineralocorticoid binding in inferior mesenteric artery showed a curvilinear pattern suggestive of the presence of two binding components, one with a higher affinity and a lower capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The presence of MR in human vasculature was first reported by Sasano et al, in 1986(Sasano et al 1986) and subsequently reported to be present not only in endothelial but also in smooth muscle cells of human vasculature (Koenig and Jaffe 2014;Nakamura et al 2006;Rizzoni et al 1996). Vascular structural remodeling in small resistance medium sized arteries was also reported in the patients with primary aldosteronism compared to essential hypertensive patients, which indicated that MR in smooth muscle cells could directly mediate the remodeling process of the vessels (Rizzoni et al 1996).…”
Section: Aldosterone Actions On Vascular Smooth Muscle Cells and Their Significance In Vasculopathymentioning
confidence: 85%
“…The presence of MR in human vasculature was first reported by Sasano et al, in 1986(Sasano et al 1986) and subsequently reported to be present not only in endothelial but also in smooth muscle cells of human vasculature (Koenig and Jaffe 2014;Nakamura et al 2006;Rizzoni et al 1996). Vascular structural remodeling in small resistance medium sized arteries was also reported in the patients with primary aldosteronism compared to essential hypertensive patients, which indicated that MR in smooth muscle cells could directly mediate the remodeling process of the vessels (Rizzoni et al 1996).…”
Section: Aldosterone Actions On Vascular Smooth Muscle Cells and Their Significance In Vasculopathymentioning
confidence: 85%
“…Since the presence of MR was first detected in the vasculature by Sasano et al, in 1986, research on the MR-mediated effects on the vasculature, including vascular smooth muscle cells (VSMC), has been ongoing [ 166 ]. RAAS components, such as ANGII and aldosterone, were frequently reported to induce oxidative stress resulting in vascular damage, such as vascular remodeling and atherosclerosis [ 167 , 168 , 169 ].…”
Section: Adrenocortical Steroids Induce Distant Cellular Senescence In Other Tissuesmentioning
confidence: 99%